2008
DOI: 10.1111/j.1365-2400.2007.00592.x
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐stocking acclimatisation of brown trout Salmo trutta: effects on growth and capture in a fast‐flowing river

Abstract: A field experiment was carried out over two consecutive years in a fast-flowing river to evaluate the effects of a 5-day acclimation period on the subsequent growth and capture of stocked juvenile brown trout, Salmo trutta L. Post-stocking growth of both acclimated and non-acclimated fish remained very poor for at least 44 to 50 days. After this slow start, all fish grew significantly but acclimated trout performed 40.1% better than nonacclimated individuals. However, the better growth did not lead to higher c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
(45 reference statements)
0
8
1
Order By: Relevance
“…Individually tagged trout harvested from NTR and EPRR consistently lost weight after stocking, and absolute growth was not correlated with size at stocking. Additionally, we did not observe an increase in growth for fish with the greatest residence time, although such an increase has been reported for Brown Trout in other systems (e.g., Baer and Brinker , ). Overall, weight loss among all trout species suggests that (1) food resources may not have been available in quantities required to maintain trout biomass at the densities stocked or (2) stocked individuals did not learn to feed on the natural prey items that were available.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Individually tagged trout harvested from NTR and EPRR consistently lost weight after stocking, and absolute growth was not correlated with size at stocking. Additionally, we did not observe an increase in growth for fish with the greatest residence time, although such an increase has been reported for Brown Trout in other systems (e.g., Baer and Brinker , ). Overall, weight loss among all trout species suggests that (1) food resources may not have been available in quantities required to maintain trout biomass at the densities stocked or (2) stocked individuals did not learn to feed on the natural prey items that were available.…”
Section: Discussioncontrasting
confidence: 80%
“…Recaptured hatchery‐reared trout typically lose weight immediately after stocking, but those that survive usually begin to grow after several months (Needham and Slater ; Miller ; Baer and Brinker , ). The observed inverse association between stream residence time and W r of stocked trout in CC and EPRR suggested that trout did not begin to grow in delayed‐harvest reaches, whereas the positive relationship between condition and density of stocked trout is likely an artifact of sample timing rather than an ecological density‐dependent effect.…”
Section: Discussionmentioning
confidence: 99%
“…To check the reliability of the tagging, in spring 2012 10 Danube streber were held for 2 weeks in two plastic mesh cube enclosures with a volume of 1 m 3 ( cf . Baer & Brinker, ), filled with autochthonous gravel from the Danube, and installed in the River Riss. Tissue was sampled from the caudal fin for genotyping ( n = 187; Table ).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, studies investigating the spatial behaviour of stocked salmonids suggest that fishes may disperse rapidly from their initial stocking location, e.g . Arctic grayling Thymallus arcticus (Pallas) (Thorfve, 2002) and brown trout Salmo trutta L. (Baer & Brinker, 2008), particularly during high‐flow events, e.g . rainbow trout Oncorhynchus mykiss (Walbaum) (Bettinger & Bettoli, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies investigating the spatial behaviour of stocked salmonids suggest that fishes may disperse rapidly from their initial stocking location, e.g. Arctic grayling Thymallus arcticus (Pallas) (Thorfve, 2002) and brown trout Salmo trutta L. (Baer & Brinker, 2008), particularly during high-flow events, e.g. rainbow trout D I S P E R S A L A N D S U RV I VA L O F S T O C K E D C Y P R I N I D S 2315 upstream fish movements, but downstream movements are possible, especially under elevated flow when a sluice gate is opened manually.…”
Section: Introductionmentioning
confidence: 99%